2022
DOI: 10.1177/21582440221129249
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Korean College of Education Pre-service Teacher Persistence Toward a Teaching Career: Quantitative Analysis of Reasons and Factors for Persisting

Abstract: Teacher attrition is a global concern. Because motivation drives a teacher to persist in their teaching career and affects their effectiveness, persistence among pre-service teachers is important. This exploratory study ( N = 55) of college of education students at a university in metropolitan Seoul, South Korea, using survey data, used (a) independent samples t-test to determine reasons for persisting and (b) correlation analysis among demographics and five persistence factors: Academic Integration, Social In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
1
0
1
Order By: Relevance
“…Another study on Swedish PSTs' professional motivations indicated that PSTs had intrinsic and altruistic motivations while choosing their careers (Bergmark et al, 2018). South Korean PSTs also demonstrated a higher frequency of extrinsic motivations than intrinsic and altruistic motivations (Murdoch & Lim, 2022). When these studies are taken into consideration, one may easily conclude that each context of study and society has its own characteristics and motivations for choosing the TC.…”
Section: Motivations For Choosing the Teaching Careermentioning
confidence: 99%
See 1 more Smart Citation
“…Another study on Swedish PSTs' professional motivations indicated that PSTs had intrinsic and altruistic motivations while choosing their careers (Bergmark et al, 2018). South Korean PSTs also demonstrated a higher frequency of extrinsic motivations than intrinsic and altruistic motivations (Murdoch & Lim, 2022). When these studies are taken into consideration, one may easily conclude that each context of study and society has its own characteristics and motivations for choosing the TC.…”
Section: Motivations For Choosing the Teaching Careermentioning
confidence: 99%
“…İngilizce öğretmenliği kariyerini seçme motivasyonlarıyla ilgili çalışmalar incelendiğinde bu motivasyonların bağlamdan bağlama değişkenlik gösterdiği anlaşılmaktadır (Bergmark vd., 2018;Murdoch & Lim, 2022). Ancak İngilizce öğretmenliği kariyerini seçme motivasyonları hizmet öncesi İngilizce öğretmeni bağlamında incelendiğinde içsel motivasyonun bu kariyeri seçme konusunda daha etkili olduğu sonucuna varılmaktadır (Smid, 2018) ve Türkiye'de yapılmış benzer bir çalışma da bunu desteklemektedir (Subaşı, 2010).…”
Section: Türkçe Geni̇şleti̇lmi̇ş öZetunclassified